Pregnancy Outcomes After ZIKV Infection in French Territories in the Americas. Issue 3 (September 2018) - Hoen, B.; Schaub, B.; Funk, A.L.; Ardillon, V.; Boullard, M.; Cabié, A.; Callier, C.; Carles, G.; Cassadou, S.; Césaire, R.; Douine, M.; Herrmann-Storck, C.; et al.
Abstract : ( N Engl J Med 2018;378:985–994) It is well recognized that Zika virus (ZIKV) infection during pregnancy can cause severe birth defects. Fortunately, the presence of centralized maternal care facilities in French territories in the Americas (French Guiana, Guadeloupe, and Martinique) allowed for enhanced surveillance of all pregnancies during the 2016 ZIKV epidemic. The authors of the present study present pregnancy outcomes in a cohort of women living in these territories who had symptomatic, laboratory-confirmed ZIKV infection during pregnancy (ZIKA-DFA-FE cohort study).